Immersive VR for K-12 experiential education – proposing a pedagogies, practicalities, and perspectives informed framework - Christian Schott; Andrea Milligan; Stephen Marshall (Computers & Education: X Reality, 2024)
Research on immersive virtual reality's (VR) impact on K-12 education, particularly experiential learning, has increased. However, there is a paucity of research providing insight into teacher and student perspectives on integrating virtually situated learning experiences (VSLE) into curricula and classrooms. This article reports on the pedagogical and practical benefits and challenges of using an immersive VSLE to support experiential learning across three K-12 schools. Focus groups with teachers and students revealed pedagogical benefits but also constraints related to classroom environments, teacher demands, and the VSLE's scale and interactivity. The findings were synthesized into an expanded conceptualisation of Situated Experiential Education Environments, incorporating nuanced pedagogical and practical considerations raised by participants.